Pelatihan Pengendalian Bahan Baku dalam Perencanaan Keuntungan Pada Bisnis Kuliner di Kota Batam - Puspita Rama Nopiana; Merline Julianti; Putu Rani Susanthi; Yelva Marsella; Ardina laia; Sallahudin Sallahudin (Universitas Maritim AMNI Semarang, 2024)
This PKM activity started with complaints from business actors about the remaining raw materials every time they opened a business. This results in losses that cannot cover the fixed costs that must always be incurred. Lecture, exercise and discussion methods are used to explain this training activity. The results of the training provide positive studies so that participants can increase their knowledge and insight into raw material control, participants can independently calculate Economic Order Quantity (EOQ) raw materials, participants can plan future profits for the business they run, participants can increase sales volume by various sales strategies in achieving sales targets. Finally, I hope this article can be developed in the next PKM training.